(untitled) (Editora Impacto Científico, 2025)
This chapter explores adolescence as a period of great creative and transformative potential, but also often marked by feelings of inadequacy and intense physical, emotional, and social fluctuations, amplified by the search for identity and belonging. From a multidisciplinary perspective, it discusses how historical, cultural, and technological contexts directly influence the ways in which adolescents perceive themselves and position themselves in the world. Authors such as Antunes & Zuin (2008), Brené Brown (2019), David Myers (2008), Paulo Freire (1996), Silvia Lane (1999), Vygotsky (1999) e Zygmunt Bauman (2001) provide the foundation for understanding adolescence as a relational and collective process in which individual and social factors intertwine. The research underpinning this chapter is guided by the following central question: How do adolescents construct their identities amid the challenges, obstacles, and potentialities present in contemporary society, marked by the fluidity of relationships and the rapid advancement of digital technologies? The hypothesis suggests that adolescents, when immersed in contexts shaped by prejudice, inequality, and social pressures, tend to experience emotional fragility and internal conflicts that may manifest in phenomena such as bullying and cyberbullying. However, when supported by empowering educational processes and safe spaces for dialogue, they can develop autonomy, empathy, and a sense of agency in building both themselves and the world around them. An integrated perspective on adolescence in contemporary society is presented, viewing it as a stage in which young people face fluid relationships, an overload of information, and internal and external demands that often hinder the formation of an authentic identity. Based on this understanding, strategies are proposed to support boys and girls in building healthy bonds and strengthening their potential, encouraging them to become transformative agents within their life contexts.